The Costs and Benefits of Shareholder Democracy: Gadflies and Low-Cost Activism - Gantchev, Nickolay; Giannetti, Mariassunta (Review of Financial Studies, 2021)
Abstract We show that there is cross-sectional variation in the quality of shareholder proposals. On average, proposals submitted by the most active individual sponsors are less likely to receive majority support, but they occasionally pass if shareholders mistakenly support them and may even be implemented due to directors’ career concerns. While gadfly proposals destroy shareholder value if they pass, shareholder proposals on average are value enhancing in firms with more informed shareholders. We conclude that more informed voting could increase the benefits associated with shareholder proposals.